제주해협을 통과하는 화학물질 플럭스 - 정창수; 홍기훈; 김석현; 박준건; 김영일; 문덕수; 장경일; 남수용; 박용철; Chung, Chang-Soo; Hong, Gi-Hoon; Kim, Suk-Hyun; et al. (Pada (Hanʼguk Haeyang Hakhoe), 2000)
The estimated total material transports through the Cheju Strait using all data which investigated in 1997 and 1999 are as follows; A large amount of suspended sediments and dissovted inorganic nutrients are carried tothe South Sea through the Cheju Strait by a persistent eastward flow (Cheju Current) from the Y311ow Sea andthe East China Sea. The annual material Oanspous by the Cheju Current are as follows; 22.9${×}$10$^6$ ton yr$^{-1}$(SS), 0.52${×}$10$^{10}$ mol yr$^{-1}$ (NH$_4\;^+$), 6.05${×}$10$^{10}$ mol yr$^{-1}$ (NO$_3\;^-$), 0.36${×}$10$^{10}$ mol yr$^{-1}$ (PO$_4\;^{3-}$), 10.27${×}$10$^{10}$ mol yr$^{-1}$ (Si(OH)$_4$). The annual suspended sediment flux per water transport in the Cheju Strait (44.48${×}$10$^6$ ton yr$^{-1}$ Sv$^{-1}$) is about 1.7 larger than that in the Korean Strait (26.08${×}$10$^6$ ton yr$^{-1}$ Sv$^{-1}$). The annual nitrate flux per water transport (11.60${×}$10$^{10}$ mol yr$^{-1}$ Sv$^{-1}$) is about 1.2 larger than that in the Korean Strait (9.72${×}$10$^{10}$ mol yr$^{-1}$ Sv$^{-1}$) and 2/3 of that by Kuroshio in the East China Sea (18.55${×}$10$^{10}$ ton yr$^{-1}$ Sv$^{-1}$). It suggests that chemical rich Cheju Current will play a significant role in the biogeochemical processes in the South Sea where the huge land-based waste are introduced. 한국 남해대륙붕에서의 물질순환을 이해하기 위해 남해연안의 보길도와 제주도를 잇는 제주해협에서 1997년부터 1999년까지 3년간 화학물질 플럭스에 대한 조사를 실시하였다. 제주해협의 입자성부유물질, 용존무기영양염류, 입자성유기탄소 및 질소는 전계절에 걸쳐 90% 이상이 동향류에 의해 황해 및 동중국해로부터 제주해협을 통해 남해로 유입된다. 제주해협을 통해 남해로 유입되는 화학물질들의 연간 플럭스는 부유물질이 22.9${×}$10$^6$ ton yr$^{-1}$, 암모니움 이온은 0.52${×}$10$^{10}$ mol yr$^{-1}$, 질산이온은 6.05${×}$10$^{10}$ mol yr$^{-1}$, 인산이온은 0.36${×}$10$^{10}$ mol yr$^{-1}$, 규산은 10.27${×}$10$^{10}$ mol yr$^{-1}$이다. 해수수송량(Sv)당 입자성부유물질 연간 플럭스는 제주해협(44.48${×}$10$^6$ ton yr$^{-1}$ Sv$^{-1}$)이 대한해협 (26.08${×}$10$^6$ ton yr$^{-1}$ Sv$^{-1}$)보다 약 1.7배 크다. 또한 제주해협 통과 질산이온 연간 플럭스(11.60${×}$10$^{10}$ mol yr$^{-1}$ Sv$^{-1}$)는 대한해협 (9.72${×}$10$^{10}$ mol yr$^{-1}$ Sv$^{-1}$)보다 약 1.2배, 동중국해에서 쿠로시오에 의한 수송량(18.55${×}$10$^{10}$ ton yr$^{-1}$ Sv$^{-1}$)에 비해서는 2/3 수준으로 높다. 결론적으로 풍부한 화학물질들을 함유한 제주해류는 남해 및 동해의 생지화학적 과정들에 있어 상당히 중요함을 시사한다.